Leisure time activities, perceived risks of drinking and selected socio-demographic variables as predictors of university students’ alcohol use - Liudmila Rupšienė; Aleksandra Batuchina; Ingrida Baranauskienė; Regina Saveljeva (Social Welfare: Interdisciplinary Approach)
Research question. Assuming if we control for the possible effect of students’ gender, age, and employment, are leisure time activities and perceived risks of alcohol use still able to predict a significant amount of the variances in students’ alcohol use? Methods. 1087 students from Lithuanian universities were selected through random sampling to complete the questionnaire on alcohol use, leisure time activities, and perceived risks of drinking. Results. Regression analyses found significant effects of age, gender, employment, some leisure time activities on university students’ alcohol use: frequency of drinking and intoxication, drunkenness last day they had drunk alcohol. In this model, the perceived risks of alcohol use were not significantly associated with alcohol use. Conclusions. Leisure time activities may offer both risk and protective effects for university students. Such leisure time activities as active participation in sports, athletics or exercising, reading of books for enjoyment, various hobbies, decreased going out in the evening to a disco, café, party, etc., and decreased socializing with friends in shopping centers, streets, parks, etc. just for fun can protect university students from frequent and heavy alcohol use.